Discretionary Accruals and COVID-19: Evidence from China - Yin, Yifei (Auckland University of Technology, 2022)
The purpose of this dissertation is to examine the effect of COVID-19 on corporate earnings management behaviour. The challenges caused by the pandemic have heavily affected the operation and business performance of companies. Based on 6,042 firm-year observations of companies listed in the Shanghai Stock Exchange and Shenzhen Stock Exchange from 2019 to 2020, this dissertation provides evidence that the use of discretionary accruals slightly increased during COIVD-19. The directionality of earnings management is mixed and subject to changes in the post-pandemic business environment. Furthermore, this dissertation explores the relationship between firm characteristics and discretionary accruals during the pandemic. The results show that smaller firms are more likely to engage in positive earnings management to boost their income and attract investors during the pandemic. Profitable firms tend to use discretionary accruals for financial performance window-dressing. Also, I find high leveraged firms tend to manage their earnings to avoid excess monitoring from lenders and debt covenant violation. There is weak evidence that firms in the essential industry may engage income-increasing earnings management. This dissertation extends limited literature on the use of discretionary accruals during the pandemic and provides insights for regulators to monitor opportunistic behaviors in the global COVID-19 epidemic situation.